Bruklighetsuppgifter i ordböcker: ett retoriskt perspektiv - Johansson, Lars-Erik (Nordiske Studier i Leksikografi, 2014)
This study examines the background of the homogenous structure of usage labels in dictionaries. A typological analysis of the rhetorical virtues (elocutionis virtutes) and the levels of style (genera dicendi) in classical rhetoric theory encompasses prescriptive as well as descriptive elements and shows that this rhetorical system, emanating from Roman rhetoric, is the base for the still used taxonomy of usage labels.